Computer information systems and industrial management : 16th IFIP TC8 International Conference, CISIM 2017, Bialystok, Poland, June 16-18, 2017, Proceedings /: 16th IFIP TC8 International Conference, CISIM 2017, Bialystok, Poland, June 16-18, 2017, Proceedings. (2017) - Unknown
No abstract available